Telemonitoring Based Waste Cooking Oil Quality Detection and Sorting System - Miftahul Huda; Farida Arinie Soelistianto; Nugroho Suharto (Politeknik Negeri Malang, 2022)
Cooking oil that is used repeatedly is called cooking oil. Due to the very high price of cooking oil, people still use used cooking oil for daily cooking, even though it is very dangerous for health and can cause a number of diseases, such as stroke, coronary heart disease, hypertension, and cancer. Parameters that are quite important to determine the quality of used cooking oil based on Indonesian quality standards of cooking oil are color parameters, pH, free fatty acid levels and turbidity. These four parameters need to be emphasized so that people can know and control the quality of used cooking oil that is suitable for reuse. In this research, a tool is made that can determine the quality of used cooking oil based on the parameters of color, pH, free fatty acid content and turbidity. The detector is equipped with a TCS3200 sensor to detect color, a pH sensor to detect pH, a conductivity sensor to detect free fatty acid levels and a turbidity sensor to detect turbidity in used cooking oil. For data transmission, the ESP32 module is used and the output data can be viewed and monitored via a 16x2 LCD and a website on a smartphone or computer. The system created has a good quality of information delivery and successful data transmission when testing delay and packet loss. The success rate of sending data from ESP32 to the Webserver is 92.4% and the average delay in sending data is 0.0025 ms.